(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Sirenomelia, which is also known as mermaid syndrome, is an extremely rare congenital developmental disorder characterized by anomalies of the lower spine and the lower limbs. Affected infants are born with partial or complete fusion of the legs1. Additional malformations may also occur including genitourinary abnormalities, gastrointestinal abnormalities, anomalies of the lumbarsacral spine and pelvis and absence or underdevelopment (agenesis) of one or both kidneys. Affected infants may have one foot, no feet or both feet, which may be rotated externally. The tailbone is usually absent and the sacrum is partially or completely absent as well. Additional conditions may occur with sirenomelia including imperforate anus, spina bifida, and heart (cardiac) malformations. Sirenomelia is often fatal during the newborn period. The exact cause of sirenomelia is unknown, most cases occur randomly for no apparent reason (sporadically). We report a case of 30 years old primi wt 115 kg, non diabetic, normotensive, euthyroid at 38 weeks pregnancy deliverd a baby with mermaid syndrome. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 144-147